The influence of utaut 1 model factors on behavioral intention to use ovo e—wallet in generation z of Bengkulu City : economy - Anggita Harahap, Ridha; Rahmayanti, Dewi (Enrichment : Journal of Management, 2023)
The progress of information technology has brought about significant changes in various aspects of human life. This study ains to investigate how performance expectancy, effort expectancy, social influence, facilitating conditions, and hedonic motivation influence the behavioral intention to embrace the OVO e-wallet among Generation Z individuals residing in Bengkulu City. The acquisition of data was conducted through a survey method involving the distribution of questionnaires to gather relevant information. The population in this study is someone who use the OVO e-wallet in the Bengkulu City area. The questionnaire collected was 130 respondents using the Hair et al, formula (2017). The sampling technique employed is purposive sampling. Afterward, the data was subjected to analysis using the Partial Least Squares (PLS) statistical method. The results indicate that among the five hypothese proposed, only two are supported. Notably, social influence and hedonic motivation show a significant positive influence on the behavioral intention to adopt the OVO e-wallet. Conversely, performance expectancy, effort expectancy, and facilitating conditions do not have an impact on behavioral intention. This suggest that additional factors night exert a more prominent influence on shaping the intention to utilize the OVO e-wallet in the given locality